2002
DOI: 10.1103/physrevb.66.245403
|View full text |Cite
|
Sign up to set email alerts
|

Ion-irradiation-induced welding of carbon nanotubes

Abstract: As recent transmission electron microscopy experiments demonstrate, electron irradiation can be used to create molecular junctions between carbon nanotubes. Employing empirical potential molecular dynamics, we study ion bombardment of crossed nanotubes as an alternative technique to join nanotubes. We demonstrate that ion irradiation should result in welding of crossed nanotubes, both suspended and deposited on substrates. We further discuss various experimental aspects of this method which may potentially be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
101
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(104 citation statements)
references
References 36 publications
2
101
0
1
Order By: Relevance
“…29 Welding of crossed SWCNTs using ion beam irradiation was demonstrated employing empirical potential molecular dynamics. 30 Authors have also suggested that ion beam irradiation potentially could be used for developing complicated networks of joined nanotubes. They concluded that welding of carbon nanotubes is not possible without structural defects.…”
Section: Resultsmentioning
confidence: 99%
“…29 Welding of crossed SWCNTs using ion beam irradiation was demonstrated employing empirical potential molecular dynamics. 30 Authors have also suggested that ion beam irradiation potentially could be used for developing complicated networks of joined nanotubes. They concluded that welding of carbon nanotubes is not possible without structural defects.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated by experimental and theoretical studies that irradiation can be used for nano-engineering of carbon nanotubes [7,8]. For example, focused electron beams were shown to result in welding of crossed single-wall carbon nanotubes to form molecular junctions [9], and molecular dynamics simulations showed how such junctions might also be produced by irradiation by Ar + ions [10]. Irradiation by 1.25-MeV electrons at high temperature (800 • C) was able to coalesce neighbouring Ndoped SWNTs as a result of defect formation followed by thermal annealing [11].…”
mentioning
confidence: 99%
“…Band gap tailoring and carbon nanotube interconnects have been achieved using charged particle beams as well. [4][5][6][7] Furthermore, it appears that it is possible to modify their physical properties by changing their structure locally only along a short section of the tube. 8 Most of the works devoted to study the effects of electron or ion-beam irradiation have involved single-walled and multiwalled carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%